Gender, Culture and Domestic Violence: Interrogating the Criminal and Penal Code in Nigeria - Bature, Elizabeth Aishatu (NIU Journal of Humanities, 2020)
Domestic violence affects women as a gendered group across all racial, national, social and economic groups. The state of the worldâ€™s population estimates that 33% of women worldwide suffer different forms of violence in different methods by various means. Domestic violence is not only an under reported crime; but when reported it is more often treated inconsequentially. Cultural rules or expectations of behaviour and norms within a cultural or social group can encourage violence. Cultural acceptance of violence either as a â€œnormalâ€ method of resolving conflict is a risk factor for all types of inter-personal violence. The Penal Code of Northern Nigeria Section 55 (1)(d) provides that an assault on a woman by her spouse is legal as much as that assault is for corrective purposes being that the woman is the said property of the man. The Criminal Code in Section 357 exempts husbands from spousal rape, while the Violence against Persons (Prohibition) Act (2015) seeks to eliminate violence in private and public life and to ensure maximum protection and effective remedies for victims. Clearly, there are contradictions in these acts. The paper intends to bring out this incongruencies and to advocate for a revision of the acts that unwittingly encourage the continued violence acts against Nigerian women. Keywords: Penal Code, Criminal Code, Gender, Culture, Domestic Violence